"Stopping for knowledge": The sense of beauty in the perception-action cycle. (November 2020) - Sarasso, P.; Neppi-Modona, M.; Sacco, K.; Ronga, I.
Highlights: Aesthetic appreciation signals optimal perceptual learning. Beauty appreciation inhibits motor behaviour to foster learning. Immobility during aesthetic appreciation favors perceptual processing. Correlates of aesthetic appreciation are similar across sensory and artistic domains. The experience of beauty motivates to tolerate uncertainty. Abstract: According to a millennial-old philosophical debate, aesthetic emotions have been connected to knowledge acquisition. Recent scientific evidence, collected across different disciplinary domains, confirms this link, but also reveals that motor inhibition plays a crucial role in the process. In this review, we discuss multidisciplinary results and propose an original account of aesthetic appreciation (the stopping for knowledge hypothesis ) framed within the predictive coding theory. We discuss evidence showing that aesthetic emotions emerge in correspondence with an inhibition of motor behavior (i.e., minimizing action), promoting a simultaneous perceptual processing enhancement, at the level of sensory cortices (i.e., optimizing learning). Accordingly, we suggest that aesthetic appreciation may represent a hedonic feedback over learning progresses, motivating the individual to inhibit motor routines to seek further knowledge acquisition. Furthermore, the neuroimaging and neuropsychological studies we review reveal the presence of a strong association between aesthetic appreciation and the activation of the dopaminergic reward-related circuits. Finally, we propose a number of possible applications of the stopping for knowledge hypothesis in the clinical and education domains.